PANDANGAN PESERTA BPJS DI KELURAHAN AIR PACAH TERHADAP PEMBERHENTIAN PELAYANAN BPJS DI RUMAH SAKIT ISLAM SITI RAHMAH TAHUN 2020 - Rika Amran; Elfahmi, Elfahmi; Adji Mustiaji; Pratiwi Ramadhani Feriza (Yayasan Nusantara Hasana Berdikari, 2023)
Social Security Administration Agency (BPJS) is a legal entity established to organize social security programs. BPJS collaborates with hospitals in order to improve service quality and health service quality. One of the hospitals that have collaborated with BPJS is RSI Siti Rahmah, which is located in Air Pacah Village, Padang. Termination of cooperation between BPJS and RSI Siti Rahmah at the end of 2019 will have an impact on the continuity of BPJS participants in Air Pacah village.The purpose of this study was to determine the views of BPJS participants in Air Pacah Village on the stop of BPJS services at RSI Siti Rahmah in 2020. The method used in this study was descriptive observation through open interviews without any intervention to the respondents. There were 10 respondents involved in this study who were BPJS participants and resisded in Air Pacah sub-district. BPJS participants in Air Pacah sub-district were disappointed with the discontinuation of BPJS services at RSI Siti Rahmah. The respondents had to find another hospital with BPJS services that farther that before. As conclusion the people are disappointed and need the nearest health facility for treatment.